Integrating water footprint and sefficiency: overcoming water footprint criticisms and improving decision making - Haie, Naim (2018)
The Water Footprint Network (WFN) methodology has emerged as a major framework of/for policy analysis as water problems increase. Being addressed by a growing body of literature, water footprint (WF) accounting has advanced substantially in recent years, whereas its sustainability assessment has lagged behind. For this and other reasons, the suitability of WF in guiding water management and planning has been criticised. Simultaneously, water efficiency has gone through much discussion and a new framework called 'sefficiency' (sustainable efficiency) has been presented. It uses a universal law (water balance) to develop systemic and comprehensive performance indicators, integrating water quantity, pollution and value to reveal their trade-offs in multi-level governance with climate descriptors and stakeholder enablers. This article revisits WF criticisms in six categories and advances the sustainability assessment phase of the WFN framework via sefficiency. Starting from, and critically reviewing, a two-country example presented by Dennis Wichelns, we illustrate, through nine (3x3) scenarios, real possibilities of integrating WF and sefficiency. The results reveal that economic and/or WF perspectives alone are insufficient to improve water decision-making processes, not necessarily guaranteeing an increase in the performance of the full system. Consequently, policy makers should be doubly careful about, for example, WF reductions, if sefficiency also decreases.